2004
DOI: 10.1300/j123v47n01_09
|View full text |Cite
|
Sign up to set email alerts
|

Everything You Always Wanted to Know About SFX but Were Afraid to Ask

Abstract: Link resolvers, including Ex Libris' SFX, use OpenURL to provide library patrons with contextsensitive links, such as the ability to move quickly from a citation in an abstracting and indexing database to the full text. In SFX, information for determining the appropriate links is maintained in the knowledge base, which contains details about a library's electronic holdings and other information about electronic information resources. This article describes SFX functionality, what the service looks like from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Further investigation revealed that those books existed in the SFX KnowledgeBase with an inactive status. In SFX, the entire database is called the "KnowledgeBase" (Robertson and Soderdahl, 2004). Ex Libris provides a global KnowledgeBase of resource templates that can be localized by an institution to match its own collection.…”
Section: The Book Citation Linkermentioning
confidence: 99%
“…Further investigation revealed that those books existed in the SFX KnowledgeBase with an inactive status. In SFX, the entire database is called the "KnowledgeBase" (Robertson and Soderdahl, 2004). Ex Libris provides a global KnowledgeBase of resource templates that can be localized by an institution to match its own collection.…”
Section: The Book Citation Linkermentioning
confidence: 99%
“…In SFX, the entire database is called the "KnowledgeBase" (Robertson and Soderdahl, 2004). Ex Libris provides a global KnowledgeBase of resource templates that can be localized and customized by an institution to match their own collection.…”
Section: Sfx Link Resolver 633mentioning
confidence: 99%
“…Articles that address the technical background and applications of SFX include those by Robertson and Soderdahl (2004), Twiss-Brooks (2003), Curran (2006), andHolman (2005). Possibly the best overview is by Cochenour, Jaramillo, and Wilde (2004).…”
Section: Previous Researchmentioning
confidence: 99%
“…They walk readers through the SFX basics, covering all the information needed to get started with SFX including terminology, the KnowledgeBase, staffing implications, and customization. The Robertson and Soderdahl (2004) article provides an overview of the technical workings of SFX and addresses its basic capabilities and terminology. Twiss-Brooks (2003) discusses the implementation of SFX at the University of Chicago, before the SFX upgrade released in 2003 that resulted in a more robust statistical component.…”
Section: Previous Researchmentioning
confidence: 99%